Professional Development of EFL Teachers in Colombia: Between Colonial and Local Practices - González Moncada, Adriana (Íkala, Revista de Lenguaje y Cultura, 2007)
The professional development of EFL teachers represents a challenge for teachers, teacher educators and policy makers in the accomplishment of better standards in education. Literature reviews on the area reveal the need for new models of professional growth for Colombian teachers. Within the framework of “Colombia Bilingüe”, the Ministry of Education proposes a professional development model that aims to reach a signifi cant number of teachers. This paper presents a critical review of this program in the light of national and international literature on teacher education. Conclusions suggest the need for more post-method approaches, for locally produced knowledge to be recognized, and for the collaborative work of policy makers and national scholars to generate teacher development programs more adequate to our reality.